Low-level laser therapy for management of large periapical lesions associated with open apex cases - Sudha Yadav; Ruchika R Nawal; Sangeeta Talwar; Mahesh Verma (Wolters Kluwer Medknow Publications, 2020)
Context: Low-level laser therapy (LLLT) is an established method to accelerate wound healing through the phenomenon of biostimulation. Aims: This case study presents a novel approach for management of open apex cases associated with large peripapical lesions using 980-nm diode laser for biostimulation. Settings and Design: Case report. Materials and Methods: Two patients presenting with open apex associated with periapical lesion were selected. After access opening, canal disinfection was carried out with sodium hypochlorite and 980-nm diode laser. Calcium hydroxide was given as intracanal medicament for 1 week. When patient was asymptomatic, apical plug of 4-5 mm MTA was placed. In addition, seven sessions of LLLT were administered transcutaneously around the apices of involved teeth every alternate day for 15 days. Results: One year follow-up radiograph revealed remarkable healing of the lesion. Conclusion: The combination of increased cellular proliferation with laser biostimulation and meticulous canal disinfection with lasers has the potential of accelerating healing of the periapical lesions.